PEMBUATAN DAN STANDARISASI ANTIGEN AI H5N1 KOMERSIAL UNTUK MONITORING TITER ANTIBODI HASIL VAKSINASI AI DI INDUSTRI PETERNAKAN AYAM - Retno D. Soejoedono; Sri Murtini; Kamalludin Zarkasie (Institut Pertanian Bogor, 2012)
Vaccination is one of the chosen strategy for controling AI H5N1 in Indonesia. Vaccination able to induce protective antibodies against AI but unable to inhibit viral infection. Determination of antibody titers in the serum from bird vaccinated with AI-H5N1 vaccine consisting of 2 or 3 different AI virus isolates difficult to be meassured if the antigen for HI test is uncalibrated yet. Furthermore, the determination of a minimum protective antibody titer against the challenge of AI virus circulating in the field at this time needs to be done. This study aims to determine the H5N1 AI virus antigen for standart HI test and the minimum titre of antibodies that able neutralize virus infection. As much as 55 chickens were divided into 11 groups, 10 groups vaccinated with commercial AI vaccine and AI H5N1 field isolat antigen. Four types of commercial vaccines were veccinated to one group and seven other groups vaccinated with the antigen AI Legok 2004, Nagrak Ag 2009, Ag Lawang 2010, as well as polyvalent Ag combination of these three types of antigen. After third vaccinations, the presence of antibodieswere meassured by HI test. Serum with a titer test 26-28 were tested for the capability of virus neutralizationin using virus neutralization test against three different H5N1 AI virus field isolates. The test results showed that the H5N1 subtype AI virus antigen representative as standart antigen for HI test is antigen Legok 2004 and the minimum titer which able neutralize H5N1 AI virus field isolates 28.